(untitled) (International Seven Journal of Multidisciplinary, 2025)
The present work addressed the relationships between organizational culture, corporate governance and knowledge management in sports organizations, highlighting how these dimensions are articulated in practice and interfere in the institutional capacity to evolve consistently. Throughout the analysis, it was observed that organizational culture works as a symbolic foundation that guides behaviors and decisions, but it can also become an obstacle when it reinforces traditional patterns that resist professionalization and innovation processes. Examples of clubs and federations that tried to implement governance practices, such as boards and audits, but faced limitations due to the lack of collective commitment and the lack of spaces for dialogue and learning, were discussed. In addition, it was found that knowledge management still does not occupy the strategic space necessary to foster the circulation of information, the systematization of experiences and the development of more creative solutions aligned with the current demands of sport. The research showed that the alignment between culture, governance and knowledge does not depend only on structural changes, but on a gradual effort to transform values and build environments that favor engagement and co-responsibility. The relevance of the theme is justified by the need to rethink practices and policies that strengthen the sustainability and legitimacy of sports organizations in a context marked by growing professionalization and the valorization of sport as an instrument of social development.